A conceptual interpretation of the relationship between leisure and its foundational disciplines: A conceptual model of leisure theory. Issue 2 (3rd May 2020) - Auger, Denis; Thériault, Gabrielle; Roult, Romain
Abstract : The multidisciplinary nature of leisure is well documented. However, few models have been developed to illustrate this reality. The objective of this paper is to present a model that conceptualizes the relationship between leisure and its foundational disciplines. According to the literature, leisure is defined as a multidimensional construct. To illustrate this construct, a review of the existing literature linking leisure and its foundational disciplines was conducted. Based on the findings, a model was created incorporating a number of concepts that suggest processes that may link leisure and its foundational disciplines. The model provides a conceptual framework for future research and theory development as well as for leisure practice. Following a detailed explanation of the model, the epistemological note focuses on the implications of the model for research, practice, and policy.